FAMILY PSYCHOEDUCATION TOWARDS ANXIETY CARING FAMILY WITH CHRONIC DISEASE AND MENTAL DISORDERS - Fredy Anggoro Tri Prayogo; Iin Noviana (Jurnal Penelitian, 2021)
Families who treat patients with chronic illnesses or mental disorders are felt as a financial and emotional burden, in addition to the lack of information to the family about the illness experienced by patients causing increased levels of family anxiety. The purpose of this study is to explain the influence of family psychoeducation on anxiety levels in caring for family members with chronic diseases and mental disorders. Research design used literature review. Journal search strategies are carried out at ProQuest, Google Scholar, Science Direct. The journal reviewed was a study of the effect of family psychoeducation on anxiety levels in caring for family members of chronic illness and mental disorders that were restricted to the past 10 years (2011-2020). A total of 516 journals that have been found are adjusted to the keywords which are then screened based on predetermined criteria. There were 11 journals that met the inclusion criteria that have been set and then conducted a review, consisting of 8 national journals and 3 international journals. From a review of journals that have been done, family psychoeducation has an effect in reducing family anxiety. Effective family psychoeducation to reduce anxiety is a psychoeducation carried out in 5 sessions, because the goals of each session can be achieved. it is expected that community psychiatric nurses are active in providing. psychoeducation therapy to families, especially with patients with chronic illnesses and mental disorders so that they can improve adaptive coping independently, and reduce anxiety in the care of sick family members.